Oxidative Intramolecular C–C Bond Formation Reactions of 1,2-Diarylbenzenes: Syntheses of Highly Conjugated Double-Bridged Polycyclic Aromatic Hydrocarbons - Islam, Md. Rafikul; Nishinaga, Tohru; Hirabayashi, Kazunori; Shimizu, Toshio; Sugiura, Ken-ichi (Synthesis, 2021)
Oxidation reactions of 1,2-diarylbenzenes induce intramolecular C–C bond formation. The substrates studied were prepared by the stepwise Suzuki–Miyaura coupling reaction that introduced 2-naphthyl, 2-anthranyl, and 2-pyrenyl groups on the ortho-positions of benzene. The subsequent oxidation reaction with FeCl3 induced an oxidative C–C bond formation reaction in the interior regions of the molecules. In marked contrast to our previous observations, two C–C bonds were formed. Theoretical calculations indicated that large spin densities at the reaction positions of the bis(cation radical) and/or cation radical species are needed for the C–C bond formation. The π-expanded molecules obtained showed bathochromic shifts in the absorption spectra.
Keywords: polycyclic aromatic hydrocarbon; oxidative C–C bond formation; FeCl3; pyrene; naphthalene; anthracene